Evaluación del impacto financiero de la aplicación del beneficio de la devolución del impuesto a la renta - Ramirez Bermeo, Mariela Fernanda (2015)
The proposal to invest the money from the refund of income tax assets acquired fixed assets aims to recover the money that corresponds to the cooperative transportation tippers Tramaco by returning the income tax to provide cash to be invested provide quality service and have control of their units corresponding to security and resources. As Bazza says Alides States are governed by laws in the form of government under the Constitution, seeking support tools to the needs, creating benefits for exemption and reduction of taxes, under the direction of the Tax Administration. The interview technique will be used to gather information for their reliability providing security in the data. The structure of implementing the proposal includes scope, time, manpower, funding to carry out the activities, describing their process and achieve conduct its realization. The financial resources obtained as a result of the return of income tax, I invested in fixed property assets, for the administrative area and security units Cooperative, being positive in the financial statements to have a control on the use of obtaining resources at their expense savings resulting in a increase in profits. Outreachprograms are recommended and inform taxpayers the procedures of applying tax benefits, and are oriented correctly so often for lack of information does not reach them believing are complicated by lack of knowledge processes.